An Accurate Discrete Current Controller for High-Speed PMSMs/Gs in Flywheel Applications - Xiang Zhang; Yunlong Chen; Yves Mollet; Jiaqiang Yang; Johan Gyselinck (Energies, 2020)
High-speed Permanent-Magnet Synchronous Motors/Generators (PMSMs/Gs) in a Flywheel Energy Storage System (FESS) are faced with high cross-coupling voltages and low switching-to-fundamental frequency ratios. High cross-coupling voltages between d-q axis current loops lead to transient current errors, which is more serious at lower switching-to-fundamental-frequency ratios. If the delays are not properly considered during the current controller design in a digital control system, the low switching-to-fundamental-frequency ratios may result in oscillatory or unstable responses. In this study, an accurate discrete current controller for high-speed PMSMs/Gs is proposed based on an accurate discrete model that takes the phase and magnitude errors generated during the sampling period into consideration, and an Extended State Observer (ESO) is applied to estimate and compensate the back EMF error. The cross-coupling problem is well settled, and the current loop dynamic at lower switching-to-fundamental frequency ratios is improved. Finally, the proposed discrete controller is validated on a 12,000 rpm PMSM/G prototype.